2016
DOI: 10.3329/jsf.v13i1.27828
|View full text |Cite
|
Sign up to set email alerts
|

Clipless Laparoscopic Cholecystectomy: An initial experience of 50 cases in Bangladesh

Abstract: Background: Laparoscopic cholecystectomy (LC) is one of the most common general surgical procedure. Objective: The purpose of the present study was to observe the surgical outcomes of the patients after clipless laparoscopic cholecystectomy. Methodology: This case series were performed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…18 Because of short area of thermal injury this can be used near vital structures; like common bile duct (CBD). Most of our patients were females (71.92%) which were similar to other studies like Saha et al 19 Harmonic scalpel reduces the duration of dissection, with little amount of mist, owing to no wastage of time in smoke evacuation and in changing of instruments. In our study the mean operative time was 24.2 minutes which was comparable to the study done by Jahangir Sarwar Khan et al 20 and Ramos et al 21 There was no bile leak from the cystic duct in our study, there was a single bile leak (0.8%) from duct of lushka which is in accordance with the other studies like Huscher et al 2 , Gelmini et al 22 , Bessa et al 23 , El nakeeb et al 24 In our case the patient was managed conservatively by ERCP and with sphinterotomy.…”
Section: Discussionsupporting
confidence: 90%
“…18 Because of short area of thermal injury this can be used near vital structures; like common bile duct (CBD). Most of our patients were females (71.92%) which were similar to other studies like Saha et al 19 Harmonic scalpel reduces the duration of dissection, with little amount of mist, owing to no wastage of time in smoke evacuation and in changing of instruments. In our study the mean operative time was 24.2 minutes which was comparable to the study done by Jahangir Sarwar Khan et al 20 and Ramos et al 21 There was no bile leak from the cystic duct in our study, there was a single bile leak (0.8%) from duct of lushka which is in accordance with the other studies like Huscher et al 2 , Gelmini et al 22 , Bessa et al 23 , El nakeeb et al 24 In our case the patient was managed conservatively by ERCP and with sphinterotomy.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported by PK Saha, Ratna Rani Roy et al in a study conducted in Bangladesh in which it was concluded that Clipless LC is a safe and effective method with no bile leak or other complications related to ligature. 14 Similarly, in another study it has been reported that the incidence of biliary leakage was statistically significantly higher in the clipped group, compared to the clipless group (30 vs. 10%, respectively; P=0.002) with a lesser median operative time in the HS group than in the Clips group (32 vs. 40 minutes, respectively; P=0.000). 6 A study by Tharwat Kandil et al concluded that clipless surgery is an effective and safe method for hemobiliary with less operative time along with decreased risk of biliary leakage and the further complications and management related with gall bladder perforation.…”
Section: Discussionmentioning
confidence: 78%
“…10 Saha et al conducted a study in Bangladesh and reported that the clipless cholecystectomy is an effective and safe method for removing gall bladder as it is associated with less incidence of gall bladder perforation and biliary leakage. 15 Another study conducted by Gelmini et al showed that mean operative time was significantly shorter in the group operated upon by the harmonic scalpel. 16 The biggest hurdle in the way of using harmonic scalpel is the requirement of expertise and expensive instruments, which are difficult to procure in a developing country like Pakistan.…”
Section: Discussionmentioning
confidence: 97%